A Silicon‐based Imidazolium Ionic Liquid Iodide Source for Dye‐Sensitized Solar Cells. Issue 3 (28th January 2013) - Wu, Wenjun; Zhang, Xiaoyu; Hu, Yue; Jin, Bin; Hua, Jianli
Abstract Room temperature molten salt 1‐methyl‐3‐(trimethylsilyl)methyl‐imidazolium iodide (MSII) was used for iodide sources in dye‐sensitized solar cells with an organic sensitizer 2‐cyano‐3‐[5‐[4‐[3‐[4‐(4‐(N, N‐bis(4‐methoxyphenyl)amino)phenyl)phenyl]‐2, 5‐di‐n‐butyl‐pyrrolo[3, 4‐c]pyrrole‐1, 4‐dione]phenyl]furan‐2‐yl] acrylic acid (DPP‐I) as light harvester. With an optimized electrolyte (MSII:I2:BI:GuNCS24:2:2:0.4, BI and GuCNS are short for benzimidazole and guanidine thiocyanate, respectively), photovoltaic parameters (Jsc, Voc, and ff) of device are 8.97 mA·cm−2, 600 mV and 0.61, respectively, yielding a maximum overall photo‐to‐energy conversion ef?ciency (η) of 3.23%. And then the charge‐transfer mechanism of devices was deeply analyzed with electrochemical impedance spectroscopy (EIS) in the dark.